2012
DOI: 10.1007/s00418-012-0949-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin and adiponectin on proliferation and protein metabolism of porcine myoblasts

Abstract: The aim of this study was to show the abundance of leptin and adiponectin receptors (LEPR, ADIPOR1, ADIPOR2) and to determine the direct effects of leptin and adiponectin on the in vitro growth of porcine skeletal muscle cells. ADIPOR1 and ADIPOR2 were abundant at mRNA and protein level in proliferating and differentiating myoblast cultures derived from semimembranosus and semitendinosus muscles of newborn piglets, whereas LEPR expression was close to the detection limit. Adiponectin (10, 20, 40 μg/ml) attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…Although leptin clearly has stimulatory effects on mouse myoblasts and muscle, it is not clear whether leptin promotes myoblast proliferation in all species. Leptin receptors are poorly abundant in porcine muscle, and recombinant leptin has no effect on proliferation of primary porcine myoblasts cultured in serum free medium or on protein accretion as these cells differentiated (Will et al, 2012). In line with this finding, lean and obese leptin receptor-deficient Zucker rats exhibit comparable BrdU incorporation, expression of myogenic regulatory factors, activation of pro-hypertrophic signaling pathways and gain of muscle mass in response to overload, demonstrating that leptin signaling per se is not required for satellite cell activation and muscle hypertrophy, at least in rats (Peterson et al, 2008a).…”
Section: Effects Of Obesity On Muscle Progenitor Cellsmentioning
confidence: 99%
“…Although leptin clearly has stimulatory effects on mouse myoblasts and muscle, it is not clear whether leptin promotes myoblast proliferation in all species. Leptin receptors are poorly abundant in porcine muscle, and recombinant leptin has no effect on proliferation of primary porcine myoblasts cultured in serum free medium or on protein accretion as these cells differentiated (Will et al, 2012). In line with this finding, lean and obese leptin receptor-deficient Zucker rats exhibit comparable BrdU incorporation, expression of myogenic regulatory factors, activation of pro-hypertrophic signaling pathways and gain of muscle mass in response to overload, demonstrating that leptin signaling per se is not required for satellite cell activation and muscle hypertrophy, at least in rats (Peterson et al, 2008a).…”
Section: Effects Of Obesity On Muscle Progenitor Cellsmentioning
confidence: 99%
“…This becomes even clearer by looking at inconsistent results of a few studies, most of them performed using rodent muscle, reporting about stimulating (Lamosova and Zeman 2001, Ramsay 2003, Yu et al 2008, Fiaschi et al 2010, inhibitory (Arita et al 2002, Wang et al 2005 or a lack of effects (Carbo et al 2000). As previously shown, long-term adiponectin and leptin treatment over 24 or 48 h appeared not to have direct effects on growth and protein metabolism of proliferating porcine myoblasts (Will et al 2012). However, the presence of growth factors in cell culture medium was suggested to be an important factor for the adipokine effects, especially of adiponectin.…”
Section: Introductionmentioning
confidence: 68%
“…For this study, recombinant porcine adiponectin produced in E. coli was used (Ledoux et al 2006). The detailed process of its obtaining was already described by Will et al (2012) and its biological activity was shown in a former study by inducing periovulatory changes in ovarian follicular cells (Ledoux et al 2006). Recombinant porcine leptin produced in E. coli was obtained from ProSpec (East Brunswick, NJ, USA).…”
Section: Sources Of Adiponectin and Leptinmentioning
confidence: 99%
“…Twentyfive micrograms of total protein were used for electrophoresis performed as previously described [14], and the following antibodies that cross-react with porcine protein were used: anti-human AdipoR1 and AdipoR2 polyclonal antibodies (Santa Cruz Biotechnology Inc, Santa Cruz, CA, USA) as previously reported [21], AMPKa and pAMPKa polyclonal antibodies, p38 MAPK and pp38 MAPK polyclonal antibodies. Antimouse PPARa and pPPARa polyclonal antibodies (Thermo Scientific, Barrington, IL, USA) were used because of high homology (96% of positive residues) of mouse PPARa with the corresponding PPARa porcine protein.…”
Section: Western Blot Analysis Of Adipor1 and Adipor2 Ampka P38 Mapmentioning
confidence: 99%